A Study of the Visual Meaning in the Comic Hai Miiko by Ono Eriko (Based on Ferdinand de Saussure's Semiotics) - Chairin, Nakita Hirda Pasha; Saragi, Daulat (Institut Seni Indonesia Padang Panjang, 2024)
This study examines the Hai Miiko comic, popular among Indonesian teenagers, which tells the story of Miiko, a cheerful fifth-grader experiencing puberty. Using Ferdinand de Saussure's semiotic theory, the research analyzes the comic's visual elements, language, and context to uncover deeper meanings and symbolism. Key concepts such as synchronic and diachronic analysis, langue and parole, signifier and signified, syntagmatic and paradigmatic structures, and denotation and connotation are applied to dissect the semiotic aspects of the comic. The findings reveal that Hai Miiko not only depicts the daily lives of teenagers but also serves as a visual representation of the journey to adulthood. Through symbolic imagery and a distinct artistic style, Ono Eriko effectively portrays emotional growth and self-discovery, inviting readers to reflect on childhood nostalgia and the challenges of growing up. This study emphasizes that comics, beyond being entertainment, can convey profound meanings and cultural insights through their visuals and narratives.